(untitled) - Wagner, Barbara (Hoboken, N.J., 2003)
In a direct and easy-to-use style, the Savvy Savings Guide series offers great financial advice for both your personal and professional life. With each new book, you'll learn how to earn more, spend less, and save for important events such as retirement and your child's college education. From paying less on your taxes to starting a small business the Savvy Savings Guide series will help you save money and succeed!
Keywords: College costs,Students,Chi phí trường Cao đẳng,Học sinh; Finance, Personal,Tài chính, cá nhân; United States,United States,Hoa Kỳ,Hoa Kỳ